1983
DOI: 10.1016/0035-9203(83)90212-2
|View full text |Cite
|
Sign up to set email alerts
|

Naegleria australiensis: experimental meningoencephalitis in mice

Abstract: Naegleria australiensis was recently described as a new species of free-living amoeba pathogenic for mice. Infections of human brain by the free-living amoebae N. fowleri and Acanthamoeba spp. are well known. We here describe the clinicopathological features of experimental infection of the central nervous system of mice by N. australiensis. Weanling mice were inoculated intranasally and intracerebrally. The involvement of the nasal mucosa, olfactory neuroepithelium and lobes, cerebrum and cerebellum was detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

1984
1984
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 14 publications
1
11
0
1
Order By: Relevance
“…Literature reviews had indicated nonpathogenic amoebas such as N. australiensis and Vannella spp. may cause diseases in animals (De Jonckheere et al. 1983; Dyková 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature reviews had indicated nonpathogenic amoebas such as N. australiensis and Vannella spp. may cause diseases in animals (De Jonckheere et al. 1983; Dyková 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Literature reviews had indicated nonpathogenic amoebas such as N. australiensis and Vannella spp. may cause diseases in animals (De Jonckheere et al 1983;Dyková 2005). Mice experimentally infected with N. australiensis developed subacute meningoencephalitis comparable to that caused by Acanthamoeba spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ITS1 sequences of different N. fowleri types l'espèce la plus étroitement apparentée à N. fowleri, bien qu'elle ne soit pas pathogène, et elle est considérée comme un indicateur de la présence possible de N. fowleri [7]. N. australiensis est pour sa part pathogène pour la souris [4,5,15], mais n'a encore jamais été détectée dans les infections humaines [7].…”
Section: Discussionunclassified
“…For example, no case of PAM associated with N. australiensis or N. italica has so far been described among humans, although these species are pathogenic for mice (15). Moreover, while many studies (6,9,18,34,39) have shown the presence of anti-N. fowleri antibodies in humans, these have not been found in laboratory animals; this may explain the greater resistance among humans.…”
Section: Discussionmentioning
confidence: 99%